ML Aggarwal Solutions for Class 9 Maths Chapter 3 – Expansions are provided here to help students prepare and excel in their exams. This chapter mainly deals with problems based on expansions. Experts tutors have formulated the solutions in a step by step manner for students to grasp the concepts easily. From the exam point of view, solving the problems on a regular basis, students can improve their conceptual knowledge. The solutions contain brief step wise explanations, which are purely based on the latest syllabus of ICSE board. Students can cross check the answers with the solutions designed by the experts and understand the other ways of solving problems effortlessly. To know more about these concepts, students can access ML Aggarwal Solutions pdf, from the links which are provided below and start practising offline to secure good marks in the board exams.

Chapter 3 – Expansions contain chapter test and the ML Aggarwal Class 9 Solutions present in this page provide solutions to questions related to each topic present in this chapter.

## Download the Pdf of ML Aggarwal Solutions for Class 9 Maths Chapter 3 – Expansions

### Access answers to ML Aggarwal Solutions for Class 9 Maths Chapter 3 – Expansions

Chapter Test

**1. Find the expansions of the following :(i) (2x + 3y + 5) (2x + 3y â€“ 5)(ii) (6 â€“ 4a -7b)**

^{2}(iii) (7 â€“ 3xy)

^{3}(iv) (x + y + 2)

^{3}

**Solution:**

**(i)** (2x + 3y + 5) (2x + 3y â€“ 5)

Let us simplify the expression, we get

(2x + 3y + 5) (2x + 3y â€“ 5) = [(2x + 3y) + 5] [(2x – 3y) â€“ 5]

By using the formula, (a)^{2} â€“ (b)^{2} = [(a + b) (a – b)]

= (2x + 3y)^{2}Â â€“ (5)^{2}

= (2x)^{2}Â + (3y)Â ^{2}Â + 2 Ã— 2x Ã— 3y â€“ 5 Ã— 5

= 4x^{2}Â + 9y^{2}Â + 12xy – 25

Â

**(ii)** (6 â€“ 4a â€“ 7 b)^{2}

Let us simplify the expression, we get

(6 â€“ 4a â€“ 7 b)^{2}Â = [ 6 + (- 4a) + (-7b)]^{2}

= (6)^{2}Â + (- 4a)^{2}Â + (- 7b)^{2}Â + 2 (6) (- 4a) + 2 (- 4a) (-7b) + 2 (-7b) (6)

= 36 + 16a^{2}Â + 49b^{2}Â â€“ 48a + 56ab â€“ 84b

**(iii)** (7 â€“ 3xy)^{3}

Let us simplify the expression

By using the formula, we get

(7 â€“ 3xy)^{3 }= (7)^{3}Â â€“ (3xy)^{3}Â â€“ 3 (7) (3xy) (7 â€“ 3xy)

Â = 343 â€“ 27x^{3}y^{3}Â â€“ 63xy (7 â€“ 3xy)

= 343 â€“ 27x^{3}y^{3}Â â€“ 441xy + 189x^{2}y^{2}

**(iv)** (x + y + 2)^{3}Â

Let us simplify the expression

By using the formula, we get

(x + y + 2 )^{3}Â = [(x + y) + 2]^{3}

= (x + y)^{3}Â + (2)^{3}Â + 3 (x + y) (2) (x + y + 2)

= x^{3}Â + y^{3}Â + 3x^{2}y + 3xy^{2}Â + 8 + 6 (x + y) [(x + y) + 2]

= x^{3}Â + y^{3}Â + 3x^{2}y + 3xy^{2}Â + 8 + 6 (x + y)^{2}Â +12(x + y)

= x^{3}Â + y^{3}Â + 3x^{2}y + 3xy^{2}Â + 8 + 6 (x^{2}Â + y^{2}Â + 2xy) + 12x + 12y = x^{3}Â + y^{3}Â + 3x^{2}y + 3xy^{2}Â + 8 + 6x^{2}Â + 6y^{2}Â + 12xy + 12x + 12y

= x^{3}Â + y^{3}Â + 3x^{2}y + 3xy^{2}Â + 8 + 6x^{2}Â + 6y^{2}Â + 12x + 12y + 12xy

**2. Simplify: (x â€“ 2) (x + 2) (x ^{2}Â + 4) (x^{4}Â + 16)**

Solution:

Let us simplify the expression, we get

(x â€“ 2) (x + 2) (x^{4}Â + 4) (x^{4}Â +16) = (x^{2}Â â€“ 4) (x^{4}Â + 4) (x^{4}Â + 16)

= [(x^{2})^{2}Â â€“ (4)^{2}] (x^{4}Â + 16)

= (x^{4}Â â€“ 16) (x^{4}Â + 16)

= (x^{4})^{2}Â â€“ (16)^{2}Â

= x^{8}Â â€“ 256

**3. Evaluate 1002 Ã— 998 by using a special product.Solution: **

Let us simplify the expression, we get

1002 Ã— 998 = (1000 + 2) (1000 â€“ 2)

= (1000)^{2}Â â€“ (2)^{2}Â

= 1000000 â€“ 4

= 999996

**4. If a + 2b + 3c = 0, Prove that a ^{3}Â + 8b^{3}Â + 27c^{3}Â = 18 abc**

Solution:

Given:

a + 2b + 3c = 0, a + 2b = â€“ 3c

Let us cube on both the sides, we get

(a + 2b)^{3} = (-3c)^{3}

a^{3}Â + (2b)^{3}Â + 3(a) (2b) (a + 2b) = -27c^{3}

a^{3}Â + 8b^{3}Â + 6ab (â€“ 3c) = â€“ 27c^{3}

a^{3}Â + 8b^{3}Â â€“ 18abc = -27c^{3}

a^{3}Â + 8b^{3}Â + 27c^{3}Â = 18abc

Hence proved.

**5. If 2x = 3y â€“ 5, then find the value of 8x ^{3}Â â€“ 27y^{3}Â + 90xy + 125.**

Solution:

Given:

2x = 3y â€“ 5

2x â€“ 3y = -5

Now, let us cube on both sides, we get

(2x â€“ 3y)^{3}Â = (-5)^{3}

(2x)^{3}Â â€“ (3y)^{3}Â â€“ 3 Ã— 2x Ã— 3y (2x â€“ 3y) = -125

8x^{3}Â â€“ 27y^{3}Â â€“ 18xy (2x â€“ 3y) = -125

Now, substitute the value of 2x – 3y = -5

8x^{3}Â â€“ 27y^{3}Â â€“ 18xy (-5) = -125

8x^{3}Â â€“ 27y^{3}Â + 90xy = -125

8x^{3}Â â€“ 27y^{3}Â + 90xy + 125 = 0

**6. If a ^{2} â€“ 1/a^{2} = 5, evaluate a^{4} + 1/a^{4}**

**Solution:**

It is given that,

a^{2} â€“ 1/a^{2} = 5

So,

By using the formula, (a + b)^{2}

^{2}â€“ 1/a

^{2}]

^{2}= a

^{4}+ 1/a

^{4}â€“ 2 [a

^{2}â€“ 1/a

^{2}]

^{2}+ 2 = a

^{4}+ 1/a

^{4}

Substitute the value of a^{2} â€“ 1/a^{2} = 5, we get

5^{2} + 2 = a^{4} + 1/a^{4}

a^{4} + 1/a^{4} = 25 + 2

= 27

**7. If a + 1/a = p and a â€“ 1/a = q, Find the relation between p and q.**

**Solution:**

It is given that,

a + 1/a = p and a â€“ 1/a = q

so,

(a + 1/a)^{2} â€“ (a â€“ 1/a)^{2} = 4(a) (1/a)

= 4

By substituting the values, we get

p^{2} â€“ q^{2} = 4

Hence the relation between p and q is that p^{2} â€“ q^{2} = 4.

**8. If (a ^{2} + 1)/a = 4, find the value of 2a^{3} + 2/a^{3}**

**Solution:**

It is given that,

(a^{2} + 1)/a = 4

a^{2}/a + 1/a = 4

a + 1/a = 4

So by multiplying the expression by 2a, we get

2a^{3} + 2/a^{3} = 2[a^{3} + 1/a^{3}]

= 2 [(a + 1/a)^{3} â€“ 3 (a) (1/a) (a + 1/a)]

= 2 [(4)^{3} â€“ 3(4)]

= 2 [64 – 12]

= 2 (52)

= 104

**9. If x = 1/(4 – x), find the value of**

**(i) x + 1/x**

**(ii) x ^{3} + 1/x^{3} **

**(iii) x ^{6} + 1/x^{6} **

**Solution:**

It is given that,

x = 1/(4 – x)

So,

**(i)** x(4 – x) = 1

4x â€“ x^{2} = 1

Now let us divide both sides by x, we get

4 â€“ x = 1/x

4 = 1/x + x

1/x + x = 4

1/x + x = 4

**(ii)** x^{3} + 1/x^{3} = (x + 1/x)^{2} â€“ 3(x + 1/x)

By substituting the values, we get

= (4)^{3} â€“ 3(4)

= 64 â€“ 12

= 52

**(iii)** x^{6} + 1/x^{6} = (x^{3} + 1/x^{3})^{2} â€“ 2

= (52)^{2} â€“ 2

= 2704 â€“ 2

= 2702

**10. If x â€“ 1/x = 3 + 2âˆš2, find the value of Â¼ (x ^{3} â€“ 1/x^{3})**

**Solution:**

It is given that,

x â€“ 1/x = 3 + 2âˆš2

So,

x^{3} â€“ 1/x^{3} = (x â€“ 1/x)^{3} + 3(x â€“ 1/x)

= (3 + 2âˆš2)^{3} + 3(3 + 2âˆš2)

By using the formula, (a+b)^{3} = a^{3} + b^{3} + 3ab (a + b)

= (3)^{3} + (2âˆš2)^{3} + 3 (3) (2âˆš2) (3 + 2âˆš2) + 3(3 + 2âˆš2)

= 27 + 16âˆš2 + 54âˆš2 + 72 + 9 + 6âˆš2

= 108 + 76âˆš2

Hence,

Â¼ (x^{3} â€“ 1/x^{3}) = Â¼ (108 + 76âˆš2)

= 27 + 19âˆš2

**11. If x + 1/x = 3 1/3, find the value of x ^{3} â€“ 1/x^{3}**

**Solution:**

It is given that,

x + 1/x = 3 1/3

we know that,

(x â€“ 1/x)^{2} = x^{2} + 1/x^{2} â€“ 2

= x^{2} + 1/x^{2} + 2 â€“ 4

= (x + 1/x)^{2} â€“ 4

But x + 1/x = 3 1/3 = 10/3

So,

(x â€“ 1/x)^{2} = (10/3)^{2} â€“ 4

= 100/9 â€“ 4

= (100 – 36)/9

= 64/9

x â€“ 1/x = âˆš(64/9)

= 8/3

Now,

x^{3} â€“ 1/x^{3} = (x â€“ 1/x)^{3} + 3 (x) (1/x) (x â€“ 1/x)

= (8/3)^{3} + 3 (8/3)

= ((512/27) + 8)

= 728/27

= 26 26/27

**12. If x = 2 – âˆš3, then find the value of x ^{3} â€“ 1/x^{3}**

**Solution:**

It is given that,

x = 2 – âˆš3

so,

1/x = 1/(2 – âˆš3)

By rationalizing the denominator, we get

= [1(2 + âˆš3)] / [(2 – âˆš3) (2 + âˆš3)]

= [(2 + âˆš3)] / [(2^{2}) â€“ (âˆš3)^{2}]

= [(2 + âˆš3)] / [4 – 3]

= 2 + âˆš3

Now,

x â€“ 1/x = 2 – âˆš3 â€“ 2 – âˆš3

= – 2âˆš3

Let us cube on both sides, we get

(x â€“ 1/x)^{3} = (-2âˆš3)^{3}

x^{3} â€“ 1/x^{3} â€“ 3 (x) (1/x) (x â€“ 1/x) = 24âˆš3

x^{3} â€“ 1/x^{3} â€“ 3(-2âˆš3) = -24âˆš3

x^{3} â€“ 1/x^{3} + 6âˆš3 = -24âˆš3

x^{3} â€“ 1/x^{3} = -24âˆš3 – 6âˆš3

= -30âˆš3

Hence,

x^{3} â€“ 1/x^{3} = -30âˆš3

**13. If the sum of two numbers is 11 and sum of their cubes is 737, find the sum of their squares.Solution: **

Let us consider x and y be two numbers

Then,

x + y = 11

x^{3}Â + y^{3}Â = 735 and x^{2}Â + y^{2}Â =?

Now,

x + y = 11

Let us cube on both the sides,

(x + y)^{3}Â = (11)^{3}

x^{3}Â + y^{3}Â + 3xy (x + y) = 1331

737 + 3x Ã— 11 = 1331

33xy = 1331 â€“ 737

= 594

xy = 594/33

xy =Â 8

We know that, x + y = 11

By squaring on both sides, we get

(x + y)^{2}Â = (11)^{2}

x^{2}Â + y^{2}Â + 2xy = 121Â ^{2}Â x^{2}Â + y^{2}Â + 2 Ã— 18 = 121

x^{2}Â + y^{2}Â + 36 = 121

x^{2}Â + y^{2}Â = 121 â€“ 36

= 85

Hence sum of the squares = 85

**14. If a â€“ b = 7 and a ^{3}Â â€“ b^{3}Â = 133, find:**

(i) ab

(ii) a^{2}Â + b^{2}

Solution:

It is given that,

a â€“ b = 7

let us cube on both sides, we get

**(i)** (a â€“ b)^{3}Â = (7)^{3}

a^{3}Â + b^{3}Â â€“ 3ab (a â€“ b) = 343

133 â€“ 3ab Ã— 7 = 343

133 â€“ 21ab = 343

â€“ 21ab = 343 â€“ 133 21ab

= 210

ab = -210/21

ab = -10

**(ii)** a^{2}Â + b^{2}

Again a â€“ b = 7

Let us square on both sides, we get

(a â€“ b)^{2}Â = (7)^{2}

a^{2}Â + b^{2}Â â€“ 2ab = 49

a^{2}Â + b^{2}Â â€“ 2 Ã— (- 10) = 49

a^{2}Â + b^{2}Â + 20 = 49

a^{2}Â + b^{2}Â = 49 â€“ 20

= 29

Hence, a^{2}Â + b^{2}Â = 29

**15. Find the coefficient of x ^{2}Â expansion of (x^{2}Â + x + 1)^{2}Â + (x^{2}Â â€“ x + 1)^{2}**

Solution:

Given:

The expression, (x^{2}Â + x + 1)^{2}Â + (x^{2}Â â€“ x + 1)^{2}

(x^{2}Â + x + 1)^{2}Â + (x^{2}Â â€“ x + 1)^{2} = [((x^{2}Â + 1) + x)^{2}Â + [(x^{2}Â + 1) â€“ x)^{2}]

= (x^{2}Â + 1)^{2}Â + x^{2}Â + 2 (x^{2}Â + 1) (x) + (x^{2}Â + 1)^{2}Â + x^{2}Â â€“ 2 (x^{2}Â + 1) (x)

= (x^{2})^{2}Â + (1)^{2}Â + 2 Ã— x^{2}Â Ã— 1 + x^{2}Â + (x^{2})^{2}Â + 1 + 2 Ã— x^{2}Â + 1 + x^{2}

= x^{4}Â + 1 + 2x^{2} + x^{2}Â + x^{4}Â + 1 + 2x^{2}Â + x^{2}

= 2x^{4}Â + 6x^{2}Â + 2

âˆ´ Co-efficient of x^{2}Â is 6.